Respiratory Function in Friedreich's Ataxia - Elena Vinante; Elena Colombo; Gabriella Paparella; Michela Martinuzzi; Andrea Martinuzzi (MDPI AG, 2022)
Background: Friedreich's ataxia is an inherited, rare, progressive disorder of children and young adults. It is characterized by ataxia, loss of gait, scoliosis, cardiomyopathy, dysarthria and dysphagia, with reduced life expectancy. Alterations of respiratory dynamics and parameters are frequently observed. However, in the literature there are few, dated studies with small cohorts. Our study aims to make an objective analysis of the respiratory condition of both early and late stage FRDA patients, looking for correlations with the motor, skeletal, speech and genetic aspects of this condition. Materials and methods: This retrospective observational study is based on the collection of clinical and instrumental respiratory data of 44 subjects between 13 and 51 years attending a tertiary rehabilitation centre in northern Italy. The analysis was carried out using Pearson's correlation test, ANOVA test and post hoc tests. Results: Data show the presence of a recurrent pattern of respiratory dysfunction of a restrictive type, with reduction in forced vital capacity and of flow and pressure parameters. The severity of the respiratory condition correlates with the disease severity (measured with disease-specific scales), with pneumophonic alterations and with the severity of the thoracic scoliotic curve. Conclusions: Respiratory function is impaired at various degrees in FRDA. The complex condition of inco-ordination and hyposthenia in FRDA affects daytime and night-time respiratory efficiency. We believe that the respiratory deficit and the inefficiency of cough are indeed a clinical problem deserving consideration, especially in the context of the concomitant postural difficulty and the possible presence of dysphagia. Therefore, the rehabilitation project for the subject with FRDA should also consider the respiratory function.